Linking ecological condition to enforcement of marine protected area regulations in the greater Caribbean region. (December 2015) - Kaplan, Katherine A.; Ahmadia, Gabby N.; Fox, Helen; Glew, Louise; Pomeranz, Emily F.; Sullivan, Patrick
Abstract: Marine protected areas (MPAs) are increasingly employed worldwide to conserve marine resources. However, information on the role of governance mechanisms, in particular those associated with compliance, in shaping ecological condition inside MPAs at the regional scale remains deficient. An exploratory data analysis was conducted to evaluate links between strategies used to promote compliance with MPA regulations (e.g. incentives and penalties) and indicators of ecological condition, including biomass and density of commercial fish species, fish functional groups and coral cover in 21 MPAs across 13 different countries and territories in the greater Caribbean region. The strategies used to promote compliance with MPA regulations were correlated with indicators of ecological condition. For example, MPAs in which a larger number of incentives and penalties are present in the governance system are associated with higher commercial fish biomass and density as compared to those with fewer penalties and incentives available to promote compliance. Although most MPAs in the greater Caribbean use penalties to enforce compliance, these results suggest incentives may also be an important governance strategy for ensuring efficacy of protected areas in conserving key species. Alternatively, the presence of a high number of penalties and incentives in governance systems may also be indicative of greater state capacity and political will in these MPAs resulting in better managed MPAs. Further research is necessary to evaluate results of the exploratory data analysis presented in this study with a more in depth analysis of the de facto use of the regulations evaluated and their efficacy. Multi-country comparisons of MPA governance and ecological indicators can help policy and decision makers maintain MPAs that most effectively achieve MPA conservation objectives.